Ruang Lingkup Studi Islam: Metodologi Studi Islam - Syifauddin; Sri Noviyanti; Maftuh Ajmain (PT. Hasba Edukasi Mandiri, 2026)
This study aims to explain the general understanding of Islamic studies, identify the fields included in the scope of Islamic studies, understand the development of Islamic studies from time to time, explain that Islamic studies not only discuss worship but also social and cultural aspects, and understand the importance of comprehending the scope of Islamic studies in facing modern life. The method used is library research with a descriptive-analytical approach to literature related to Islamic studies. The results show that the scope of Islamic studies is very broad, covering the study of the Qur'an, hadith, Islamic theology, Islamic law, Islamic history and civilization, Islamic philosophy, Sufism, Islamic education, as well as Islamic social and cultural studies. The development of Islamic studies from time to time shows an evolution from classical text-based studies toward interdisciplinary and integrative approaches in the contemporary era. Understanding the scope of Islamic studies is very important in the modern era to face the complexities of globalization, maintain the relevance of Islamic teachings in multicultural societies, and address contemporary social issues.